Don Quixote de la Corte - Eyal Katvan; Boaz Shnoor (Oñati Socio-Legal Series, 2021)
Serial litigants are a well-known phenomenon. This article deals with this phenomenon on two different levels using Israel as a test-case. First, we analyze the impact they have on the judicial system as a whole, and the institutional responses the judicial system uses in order to deal with serial litigants as well as the impact (both positive and negative) such serial litigants have on other litigants. Second, we analyze the personal motives of serial litigants and identify their common denominators, as well as what differentiates them. In this regard the article offers a unique approach by presenting the perspective of serial litigants and the human dimension behind their claims. We then show that serial litigants do not constitute a monolithic group, and suggest that courts have to take the differences between them into account. We further propose the formulation of systemic tools that take into account both the negative and the positive aspects of serial litigants in order to strike a proper balance between the optimal allocation of resources, and the right of access to justice.